Trend inflation, Taylor principle and indeterminacy - Guido Ascari; Tiziano Ropele (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2005)
In this paper, we show that low trend inflation strongly affects the dynamics of a standard Neo-keynesian model where monetary policy is described by a standard Taylor rule. In particular, we show that trend inflation: (i) enlarges the indeterminacy region in the parameter space, substantially altering the so-called Taylor principle; (ii) changes the dynamic responses of the economy. Furthermore, we generalize the basic analysis to different types of Taylor rules, inertial policy rules and indexation schemes. The key point is that, whatever the set up, the literature on Taylor rules cannot disregard average inflation in both theoretical and empirical analysis.
Keywords: E24; E32; 330; Sticky Prices; Taylor Rules and Trend Inflation; Preisrigidität; Inflation; Taylor-Regel; New-Keynesian Phillips Curve; Theorie